DEVELOPING INFORMATION SYSTEM OF MANAGEMENT ARCHIEVING CORRESPONDING MAIL BASED ON WEBSITE - Dimas Fanny Hebrasianto Permadi (JOSAR (Journal of Students Academic Research), 2019)
Administration is part of the institution authorized to handle documents and archiving. The archiving mail is required for management mail data. The problem is the mail archiving still using hardfile like the result of print out from Office Application such as Microsoft Word. The archiving mail is like writing the data on incoming and outgoing mail in the report’s book. Because of that, The management of letters using the print out is oftenerrors in storing mail data. Applications corresponding aims to change the way storage is hardfile letter into tangible softfile mail archives, making it easier to perform archiving these letters as a database.This application is built using waterfall method which the plot carried out gradually. The result of this application is the officer used this application more helpful for correspondences and improve the satisfaction level of its work is increasing by12.19 % from83.13% for manually to the digitally at 83.13.